Antimicrobial, antiparasitic and anticancer properties of Hibiscus sabdariffa (L.) and its phytochemicals: in vitro and in vivo studies - Hassan, Sherif T S; Berchová, Kateřina; Šudomová, Miroslava (Ceska a Slovenska farmacie, 2016)
UNLABELLED: In the last few decades, Hibiscus sabdariffa L. (Malvaceae; H. sabdariffa) has gained much attention in research field because of its potentially useful bioactivity as well as a great safety and tolerability. For decades, microbial, parasitic and cancer diseases remain a serious threat to human health and animals as well. To treat such diseases, a search for new sources such as plants that provide various bioactive compounds useful in the treatment of several physiological conditions is urgently needed, since most of the drugs currently used in the therapy have several undesirable side effects, toxicity, and drug resistance. In this paper, we aim to present an updated overview of in vitro and in vivo studies that show the significant therapeutic properties of the crude extracts and phytochemicals derived from H. sabdariffa as antimicrobial, antiparasitic, and anticancer agents. The future directions of the use of H. sabdariffa in clinical trials will be discussed. KEY WORDS: Hibiscus sabdariffa L. antimicrobial agents cancer preventive agents antiparasitic drugs natural products.
Keywords: Hibiscus; fytonutrienty; Anti-Infective Agents; fytoterapie; protinádorové látky; zvířata; Humans; Plant Extracts; antiinfekční látky; rostlinné extrakty; Antineoplastic Agents; Phytochemicals; lidé; Phytotherapy; Animals